Copper coordination compounds with (5Z, 5Z′)-2, 2′-(alkane-α, ω-diyldiselenyl)-bis-5-(2-pyridylmethylene)-3, 5-dihydro-4H-imidazol-4-ones. Comparison with sulfur analogue. Issue 12 (2nd March 2022) - Finko, Alexander V.; Sokolov, Anatolii I.; Guk, Dmitry A.; Tafeenko, Victor A.; Moiseeva, Anna A.; Skvortsov, Dmitry A.; Stomakhin, Andrei A.; Beloglazkin, Andrei A.; Borisov, Roman S.; Pergushov, Vladimir I.; Melnikov, Mikhail Ya.; Zyk, Nikolay V.; et al.
Abstract : Mono- and binuclear Cu(+1/+2) complexes of bis-5-(2-pyridyimethylene)-2-selenohydantoins were obtained by the reactions of corresponding ligands with copper(+2) chloride or perchlorate in BuOH/DCM mixtures. Abstract : A series of new organic ligands (5 Z, 5 Z ′)-2, 2′-(alkane-α, ω-diyldiselenyl)-bis-5-(2-pyridylmethylene)-3, 5-dihydro-4 H -imidazol-4-ones (L ) consisting of two 5-(2-pyridylmethylene)-3, 5-dihydro-4 H -imidazol-4-one units linked with polymethylene chains of various lengths ( n = 2–10, where n is the number of CH2 units) have been synthesized. The reactions of these ligands with CuCl2 ·2H2 O and CuClO4 ·6H2 O gave Cu 2+ or Cu 1+ containing mono- and binuclear complexes with Cu2 L Cl x ( x = 2–4) or CuL (ClO4 ) y ( y = 1, 2) composition. It was shown that the agents reducing Cu 2+ to Cu 1+ in the course of complex formation can be both a ligand and an organic solvent in which the reaction is carried out. This fundamentally distinguishes the selenium-containing ligands L from their previously described sulfur analogs, which by themselves are not capable of reducing Cu 2+ during complexation under the same conditions. A higher cytotoxicity and reasonable selectivity to cancer cell lines for synthesized complexes of selenium-containing ligands was shown; unlike sulfur analogs, ligands L themselves demonstrate a high cytotoxicity, comparable in some cases to the toxicity of copper-containing complexes.